Pengembangan Instrumen Eksplorasi Karier Remaja: Analisis Model RASCH - Awaliyah, Annisa Mumtaz; Supriatna, Mamat; Saripah, Ipah (Universitas Muhammadiyah Metro, 2023)
Career exploration is one of the stages of individual career development. This study discusses the development of an instrument for career exploration measuring. The instrument was tested on 195 Madrasah Aliyah students in Bandung. Instruments were analyzed using the RASCH Model, with a Cronbach Alpha was 0.76, which was in the excellent category, item reliability was 0.98, which was in the special category, and person reliability was 0.72, which was in the good category. So it can be concluded that this career exploration instrument can be used for further research.